KEBERHASILAN MEDIASI DALAM PENYELESAIAN CERAI TALAK DI PENGADILAN AGAMA SALATIGA : STUDI KASUS PERKARA NOMOR 353/PDT.G/2023/PA.SAL - Kurniawan, Adhi; Mustolich, Muhammad; Nor Hidayati, ST; Sodiq, Nur; Zumrotun, Siti (LPPM STAI Muhammadiyah Probolinggo, 2025)
ABSTRACT Talaq divorce cases in the Religious Courts often become a challenge in maintaining a balance between the rights and obligations of husband and wife and the interests of children. Mediation is an alternative dispute resolution instrument used in the divorce process, including divorce and divorce, which aims to reach a peaceful agreement through the judicial process (litigation). In Supreme Court Regulation (Perma) 1 of 2016 concerning Mediation Procedures in Court, this regulation requires every civil case submitted to court to go through a mediation process first before proceeding to the further trial stage. The aim is to encourage peaceful, faster and cheaper dispute resolution through dialogue between the parties facilitated by a mediator. This article aims to examine the role of mediation in resolving talak divorce cases, as well as the factors that influence its success. A case study of a talak divorce case which succeeded in reaching an agreement through mediation will be used as material for analysis, namely case Number 353/Pdt.G/2023/PA.Sal. This research highlights the importance of mediation as a solution approach to minimize the negative impacts of divorce, especially for women and children. Keywords: Mediation; Divorce Divorce; Religious Court; Agreement